Design of OSH interventions: A model to improve their actual implementation. (June 2019) - Masi, Donato; Cagno, Enrico; Farne', Stefano; Hasle, Peter
Highlights: The implementation of OSH interventions is often difficult especially in SMEs. This paper provides a model for the systematic design and implementation of OSH interventions. The performance of the model has been tested through fifty interviews. The test of the model suggests the value of following a structured framework. Abstract: Background: A multitude of Occupational Safety and Health (OSH) interventions have proven to be effective under controlled conditions, but their implementation in practice is often difficult and interventions may therefore not work as expected, especially when referring to Small and Medium sized Enterprises (SMEs). Methods: In order to solve this challenge, this paper proposes a model for the systematic design of OSH interventions that takes into account the underlying mechanisms and the contextual factors that can enable or disable the behavioural changes needed for an effective implementation of OSH interventions. The performance of the model has been evaluated through fifty interviews. Results: The interviewees highlighted how the model fosters innovative and more effective solutions, a more effective focus on the aspects that should be considered, a more organic and systematic way of structuring the data, and a holistic and comprehensive view of the factors. The model also highlights specific aspects of contextual factors and mechanisms and it organizes the data in a more systematic and structured fashion. Conclusion: The evaluation of the model suggests the value of following a structured framework towards implementation of OSH interventions based on the analysis of mechanisms and contextual factors.